BLENDED LEARNING; INCORPORATING MOODLE INTO CLASSROOM READING COMPREHENSION ACTIVITIES : A Case Study At A Senior High School In Pangkal pinang - Wantoro, Sri (2014)
This study investigates the use of moodle to support face-to-face classroom reading-comprehension activities since managing reading as single classroom reading activity is not sufficient. Teacher needs to enable students to read outside the classroom (Lems et al., 2010). This can be realized by incorporating moodle in teaching-learning activities as a form of blended-learning. More specifically, this study examined (1) how moodle was developed to support classroom reading comprehension activities, (2) how moodle shaped students' learning environment in blended learning context, and (3) what advantages and disadvantages of incorporating moodle were to support classroom reading comprehension activities. This study employs qualitative research design (Yin, 2003; Hancock & Algozzine, 2006). Students at one of senior high schools in Pangkalpinang are participants in this study. This study employed four techniques in data collection; they were observation, interview, questionnaires, and document analysis. Data from observations were analyzed qualitatively (Hancock & Algozzine, 2006) to investigate their actual interaction in incorporating moodle for reading comprehension activities. Data from interviews were transcribed and analyzed simultaneously to find pattern of themes that emerge during and after data analysis (Kvale, 1996; Hancock & Algozzine, 2006) in accordance to research questions. Data from questionnaires were analyzed by using Likert Scales. Data from document analyses-in the form of students' portfolio in reading activities stored in moodle platform¬-were used as a part of data triangulation to see the students' reading process. The study reveals that three moodle features, Forum, Quiz, and grade are developed to support classroom-reading comprehension activities. Moodle shapes students' reading learning environment through three phases (online preview, onsite instruction, and online lab tutorial) of utilizing moodle platform in blended learning context. Students' attitude toward the use of moodle for reading comprehension activities is positive. It means that moodle facilitated them in learning process, supported their outside classroom learning activities, supported classroom reading-comprehension activities, was a new way in learning English, supported social interaction among students-students, students-teacher, and teacher-students. Based on the findings above, it is recommended that moodle is an alternative technique to support face-to-face classroom reading comprehension activities in blended learning context Penelitian ini mengkaji tentang pemanfaatan moodle untuk mendukung kegiatan pembelajaran tatap muka membaca pemahaman karena pengajaran membaca yang dilaksanakan hanya didalam kelas belumlah cukup. Guru perlu mendorong siswa untuk membaca diluar kelas (Lems et al., 2010). Ini dapat direalisasikan dengan memanfaatkan moodle dalam kegiatan belajar mengajar dalam bentuk blended learning. Lebih spesifiknya, penelitian ini mengkaji (1) bagaimana moodle dikembangkan untuk menunjang kegiatan pembelajaran membaca pemahaman didalam kelas, (2) bagaimana moodle membentuk lingkungan belajar siswa dalam kontek blended learning, dan (3) apa kelebihan dan kekurangan memanfaatkan moodle untuk mendorong pembelajaran membaca pemahaman tatap muka didalam kelas. Penelitian ini menggunakan model penelitian kualitatif (Yin, 2003; Hancock & Algozzine, 2006). Siswa-siswi di salah satu SMA di Pangkalpinang sebagai partisipan dalam penelitian ini. Penelitian ini menggunakan empat tehnik dalam pengumpulan data; observasi, wawancara, angket, dan analisis dokumen. Data dari observasi dianalisa secara kualitatif (Hancock & Algozzine, 2006) untuk menginvestigasi interaksi yang terjadi dalam proses pembelajaran dengan menggunakan moodle untuk pembelajaran membaca pemahaman. Data dari wawancara ditrasnkrip dan dianalisa secara terus menerus untuk menemukan pola tema yang serupa selama proses penelitian (Kvale, 1996; Hancock & Algozzine, 2006) berkesesuaian dengan pertanyaan penelitian. Data dari angket dianalisa dengan menggunakan sekala Likert. Data dari analisa dokumen-dalam bentuk portofolio siswa dalam proses membaca pemahaman yang tersimpan di dalam moodle-digunakan sebagai bagian dari triangulasi data untuk melihat process membaca pemahaman siswa. Ditemukan dalam penelitian ini tiga fitur moodle forum, quiz dan grade dikembangkan untuk mendukung proses pembelajaran membaca pemahaman didalam kelas. Moodle membentuk lingkungan pembelajaran membaca pemahaman melalui tiga tahapan, yakni: online preview, onsite instruction, dan online lab tutorial. Sikap siswa terhadap pemanfaatan moodle untuk mendukung proses pembelajaran membaca pemahaman positif. Ini berarti bahwa moodle memfasilitasi siswa dalam proses pembelajaran, mendorong pembelajaran diluar dan di dalam kelas, adalah cara belajar baru, mendorong interaksi sosial antar siswa dengan siswa, siswa dengan guru, dan guru dengan siswa. Berdasarkan penemuan diatas, direkomendasikan bahwa moodle adalah salah satu pilihan cara dalam pengajaran untuk mendorong kegiatan pembelajaran membaca pemahaman tatap muka di dalam kelas dalam kontek blended learning.